Comparison of magnetron sputtering systems for high-rate deposition of thick copper layers for microelectronic applications - M. V. Nazarenko (Российский технологический журнал)
Objectives. When designing production equipment for the implementation of metal film deposition processes, the selection of technological sources for providing the required quality (structure, appearance), maximum process efficiency, and productivity, poses a challenging task. Since laboratory results often differ from issues faced in production processes, this choice becomes even more difficult under real production conditions due to a lack of sources for comparison. The purpose of the present work is therefore to compare magnetron deposition methods under real industrial conditions (planar extended magnetron, liquid-phase magnetron and cylindrical magnetron with a rotating cathode), identify their advantages and disadvantages along with features of thus-formed metal films, analyze the economic feasibility of each variant, and give practical recommendations for selecting a source when implementing the described process.Methods. Films were deposited using magnetron sputtering system. Roughness was measured using a MarSurf PS1 profilometer. The structure of the films was studied using a Hitachi SU1510 scanning electron microscope. Film thicknesses were measured by X-ray fluorescence analysis using a Fisherscope X-RAY XDV-SDD measuring instrument.Results. Sources of magnetron sputtering for the high-rate deposition of metallization layers under industrial conditions are considered. Obtained samples were compared according to the following criteria: deposition rate while maintaining the required quality, surface defects, film grain size, roughness, uniformity of the deposited layer, deposition efficiency (the ratio of the metal deposited directly onto the substrate to the amount of metal produced during the process). A comparison of the characteristics showed that the deposition rate for the liquid-phase magnetron is commensurate with the similar parameter for the cylindrical magnetron, exceeding the rate for the classical planar magnetron by about 4 times while maintaining the uniform appearance of the samples. The samples deposited with a liquid-phase magnetron had the highest roughness and the largest grain size. Although the cheapest method, liquid-phase magnetron sputtering achieved the lowest sputtering efficiency.Conclusions. The choice of the deposition method depends on the problem to be solved. The rotatable magnetron system can be considered optimal in terms of cost, deposition rate, and quality of the deposited layers. Liquid-phase magnetron sputtering is recommended for low-cost high-speed deposition where there are no strict requirements for appearance, or in case of operation of small-sized equipment.